Dynamics of Work Motivation: Unveiling the Mediating Role in the Relationship Between Organizational Culture, Work Environment, and Job Promotion on Employee Performance - Martini, Ni Nyoman Putu; Nafi'ah, Nailatul Ilmi; Qomariah, Nurul; Sari, Mutiara Dwi (Jurnal Aplikasi Manajemen, 2024)
The implementation of the job transfer has made the work environment less conducive when the regulation is applied. Government organizations must be prepared in terms of institutions, policies, and new work procedures, especially in local governments, to improve performance in response to new regulations. This study aims to determine the influence of organizational culture, work environment, and job promotion on employee performance with work motivation as a mediator. This research is designed in the form of quantitative research with a causal research type. The population in this study is all Civil Servants in Banyuwangi Regency with a sample of 142 employees. The sampling technique uses non-probability sampling with a purposive sampling technique. The data in this study were obtained through a survey method using a questionnaire media. Data analysis techniques use partial least squares. The study found that organizational culture, work environment, and job promotion all have a positive and significant impact on employee performance. Additionally, organizational culture, work environment, and job promotion also positively influence work motivation. Furthermore, work motivation itself has a positive and significant effect on employee performance. It was also observed that work motivation serves as a mediator in the relationship between organizational culture and employee performance, as well as between the work environment and employee performance, and between job promotion and employee performance. This can be achieved by awarding employees who perform well, adhering to established working hours, creating a comfortable work environment where employees can enjoy their work, and providing adequate supporting facilities and resources.